Pengaruh Kepemimpinan Instruksional dan Iklim Sekolah terhadap Kepuasan Kerja Guru pada Sekolah Dasar Negeri Se-Kecamatan Pamijahan Kabupaten Bogor - Aji Aji; Qowaid Qowaid; M Faqihuddin (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
The principal is an important leader at the school level. They have many functions of daily work at school to improve the teaching and learning process. However, the reality is that many school principals are apparently too busy with all the daily responsibilities in managing and running a school. This gives the impression that the principals must give a lot of attention to becoming instructional leaders because this can help a lot both in the teaching and learning process which can lead to the quality of education. In addition, the school is an organization that has certain objectives that must be achieved. To achieve this goal, the climate of the school organization is very important. On the basis of the above, it is clearly seen that job satisfaction of a teacher is determined by at least two supporting variables, including the leadership of the school principal and the school climate. Based on these ideas the researcher is interested in conducting a study conducted to reveal two variables that are significantly related. The purpose of this study was to determine the effect of instructional leadership style and school climate both partially, and together with the teacher's job satisfaction. The approach in this research is a quantitative approach. The unit of analysis in this study was the Public Elementary School in Pamijahan sub-district, Bogor Regency, while the respondents consisted of PNS SDN teachers in Pamijahan, Bogor Regency. Based on the results of a simple regression test, from the calculation results obtained t count of 2.786 while the table at the level of confidence α = 0.05 with dk = 48 is equal to 2.010. Based on the results of testing the significance of the correlation shows that tcount> ttable (2.786> 2.010). Thus the research hypothesis which states that there is a positive influence of instructional leadership (X1) on teacher job satisfaction (Y) is proven true. From the calculation results obtained t count of 3.832, while t table at the level of confidence α = 0.05 with dk = 48 is equal to 2.010. Based on the results of testing the significance of the correlation shows that t arithmetic> t table (3,832> 2,010). Thus the research hypothesis which states that there is a positive influence of the school climate (X2) on teacher job satisfaction (Y) is proven to be true. Furthermore, based on multiple regression tests Based on the results of the significance test of multiple linear regression equations obtained Fcount of 7.199 while Ftable for the denominator 2 and numerator 47 for the level of trust α = 0.05 of 3.20 which means the value of Fcount> Ftable (7.199> 3.20) . This shows that Ho was rejected, meaning Ha who stated there was a positive influence of instructional leadership and school climate together on teacher job satisfaction was acceptable. Keywords: Instructional Leadership, School Climate and Job Satisfaction Teacher.